RESEARCH AND INNOVATION ACTIVITY OF THE STAVROPOL STATE AGRARIAN UNIVERSITY: TENDENCIES AND RESULTS - Vitaliy Yu. Morozov; Yuliya A. Bezgina; Vladimir V. Samoylenko (Высшее образование в России)
The article describes approaches to stimulate the development of innovations and science at the Stavropol State Agrarian University on the example of R&D Department. This center promotes scientific-research and innovative activities of the teaching staff, postgraduates and students, provides the coordination and organization of the innovative activities at the University, cooperation of the University with ministries and departments, agricultural enterprises and business structures of the Northern Caucasus Federal District. Particular attention is paid to the interaction system between scientists and consumers. This system includes special algorithms of grant and project financing, intellectual property protection, publication of the results of scientific andtechnical activities. Statistic information about the University scientists’ participation in the innovation process is given.